Social and Economical Empowerment of Rural Women Through Self Help Group Formation in Jaipur District of Rajasthan - Smita Bhatnagar and S S Rathore (Journal of Krishi Vigyan, 2015)
Women play an active role in agriculture, a strong need was felt to organize them into a group to bring out and improve their talent. The feedback obtained from the trainees of KVK sufficiently indicated that the impact of trainings and knowledge acquired by them during various training courses did not bear sustainable effects to bring about a desirable change in their standard of living. Hence, it was felt to organize the women and build a platform where regular interactions may sufficiently revamp their thinking and motivate their self-help spirit. KVK, Chomu emphasized the concept of social and economic empowerment of rural women through formation of self help groups. The members were trained in specific technologies, based on which they were engaged in income generating activities. The savings earned through various economic activities were utilized for meeting the needs of members. In spite of various constraints, the group could effectively function